2013
DOI: 10.1021/ja403368b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Tetragonal and Orthorhombic Polymorphs of Hf3N4 by High-Pressure Annealing of a Prestructured Nanocrystalline Precursor

Abstract: Hf3N4 in nanocrystalline form is produced by solution phase reaction of Hf(NEtMe)4 with ammonia followed by low-temperature pyrolysis in ammonia. Understanding of phase behavior in these systems is important because early transition-metal nitrides with the metal in maximum oxidation state are potential visible light photocatalysts. A combination of synchrotron powder X-ray diffraction and pair distribution function studies has been used to show this phase to have a tetragonally distorted fluorite structure wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 56 publications
2
36
0
Order By: Relevance
“…5 shows that peak positions do not maintain this cubic geometry at lower temperature, specifically the angle between the 111 and 200 reflections becomes larger. This type of distortion has been previously observed in Hf 3 N 4 , where it was initially described in terms of a rhombohedrally distorted defect rocksalt lattice [46] and later found to be due to a tetragonally distorted defect fluorite lattice [40]. No specific distortion was found that 8 modelled these molybdenum nitride samples well.…”
Section: Pyrolysis Of the Imide Polymer Precursorsupporting
confidence: 69%
See 1 more Smart Citation
“…5 shows that peak positions do not maintain this cubic geometry at lower temperature, specifically the angle between the 111 and 200 reflections becomes larger. This type of distortion has been previously observed in Hf 3 N 4 , where it was initially described in terms of a rhombohedrally distorted defect rocksalt lattice [46] and later found to be due to a tetragonally distorted defect fluorite lattice [40]. No specific distortion was found that 8 modelled these molybdenum nitride samples well.…”
Section: Pyrolysis Of the Imide Polymer Precursorsupporting
confidence: 69%
“…The surprising finding is that the two precursors result in very different molybdenum nitride phase behaviours. Our general interest in such reactions stems from the potential to access higher metal oxidation states [38,39,40] and to make controlled material morphologies [41]. Herein we targeted small particle molybdenum nitride samples that may act as good charge storage materials and tested their performance as electrodes in aqueous electrochemical capacitors.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, hafnium nitrides (HfN x ), display high melting points (HfN: 3330 ℃ [1]), high incompressibility (HfN: B 0 =260-306 GPa [2]; Hf 3 N 4 : B 0 = 227-260 GPa [3,4]), oxidation resistance at high temperature [5] and superconductivity (HfN: T c =8.8 K) [6], and have been widely exploited by experiments [7][8][9][10] and calculations [8][9][10][11] in recent years.…”
mentioning
confidence: 99%
“…1). 7 Increasing the pressure to 20 GPa and carrying out extended heating to 2000 K resulted in a new crystalline diffraction pattern that we identified as an orthorhombic cotunnite-type phase, containing 25% vacancies distributed along with N 3-ions on the anion sites (Fig. 2).…”
Section: Methodsmentioning
confidence: 85%
“…7 Its diffraction pattern showed only a broad, diffuse signal indicative of an amorphous or nanocrystalline material. Based on our structural solution for the phase that crystallized at moderate P and T (see later) we analysed the local structure of the nanocrystalline starting compound that was thought previously to be based on a rocksalt (NaCl) arrangement of ions.…”
Section: Methodsmentioning
confidence: 99%